A study on pregnancy outcome in patients with first trimester vaginal bleeding - H. S., Kavyashree; K., Rajeshwari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Vaginal bleeding is a common obstetric problem and a cause of anxiety and worry both to patients and the Obstetrician. The common cause of bleeding in 1st trimester include various types of abortion, ectopic pregnancy and molar pregnancy. This study was conducted to assess the maternal and perinatal outcome in pregnant women who present with first trimester vaginal bleeding. Methods: A Prospective study (Longitudinal study) among pregnant women presenting with First trimester bleeding was conducted for a period from November 2017 to Jan 2019 at Mysore Medical College and Hospital 200 subjects were included into the study by Multiphasic sampling method using a structured questionnaire to collect the data. Results: The study observed that among 200 subjects who were included in the study 123 (61.5%) were non-viable pregnancy and 67 (38.5%) were viable pregnancy. Among 67 viable pregnancy only 30 (47%) had no obstetrical complications, 11 (17.1%) aborted and others had problems of PROM, Preterm labour, Placenta previa, IUGR and IUD. Conclusions: It can be concluded that first trimester bleeding is a predicting factor for obstetric and perinatal complications during pregnancy. Hence it is necessary to increase the knowledge of pregnant women in this regard for closer care. It is also important factor for clinician to be attentive towards first trimester bleeding in providing clinical interventions for the continuation of pregnancy and also reducing the fetal complications in these high-risk pregnancies.